Representasi Fenomena Quarter Life Crisis pada Lirik Lagu Album Daur Hidup Karya Donne Maulana - Yuliana, Rissa; Nusivera, Egi (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This research is urgent because Donne Maulana's album "Daur Hidup" incorporates implied meanings regarding the turmoil of his life within its lyrics. This research intends to examine how the language in the lyrics of Donne Maulana's album "Daur Hidup" portrays the quarter life crisis phenomenon. This study employs qualitative research utilizing a qualitative descriptive approach, which includes analysis, explanation, and description of different conditions and situations found in the gathered data to deeply investigate the phenomenon of quarter life crisis depicted in song lyrics. Data dalam penelitian ini berupa data lisan atau tertulis dalam bentuk lirik lagu dari album "Daur Hidup" oleh Donne Maulana, serta sumber data dari 9 lagu yang terdapat dalam album "Daur Hidup" tersebut. Methods and processes for data gathering involve reading and writing. The study's results suggest that the lyrics of Donne Maulana's album "Daur Hidup" accurately portray the quarter life crisis, as evidenced by the signs and indicators present in the song lyrics and the internal factors affecting this phenomenon.